2016
DOI: 10.1177/1757975916647008
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive capacity assessment tool for non-communicable diseases in low- to middle-income countries: development and results of pilot testing

Abstract: Non-communicable diseases (NCDs) are the leading causes of death worldwide, with higher rates of premature mortality in low- and middle-income countries (LMICs). This places a high economic burden on these countries, which usually have limited capacity to address this public health problem. We developed a guided self-assessment tool for describing national capacity for NCD prevention and control. The purpose of this tool was to assist countries in identifying key opportunities and gaps in NCD capacity. It was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…The relatively large number of non-physician health workers in PHCs in this study, including CHEWs, may be partially attributed to the cumulative density of schools of health technology, which are training institutions for CHEWs in Nasarawa, Kogi, Kaduna, and Niger states, that share boundary with the Federal Capital Territory [ 18 ]. This contrasts with the 2018 report from Garcia de Quevedo et al, who identified limited NCDs workforce as a challenge in Mozambique, Colombia, and the Dominican Republic based on the high rate of temporary contract workers for NCD-related care [ 19 ]. Moucheraud reported low staff and training readiness scores for NCD diagnosis and management using Service Provision Assessment surveys across PHCs in Bangladesh (24%), Haiti (29%), Malawi (18%), Nepal (4%), and Tanzania (12%) [ 20 ], signifying that low staff and service delivery readiness is common throughout LMICs.…”
Section: Discussionmentioning
confidence: 86%
“…The relatively large number of non-physician health workers in PHCs in this study, including CHEWs, may be partially attributed to the cumulative density of schools of health technology, which are training institutions for CHEWs in Nasarawa, Kogi, Kaduna, and Niger states, that share boundary with the Federal Capital Territory [ 18 ]. This contrasts with the 2018 report from Garcia de Quevedo et al, who identified limited NCDs workforce as a challenge in Mozambique, Colombia, and the Dominican Republic based on the high rate of temporary contract workers for NCD-related care [ 19 ]. Moucheraud reported low staff and training readiness scores for NCD diagnosis and management using Service Provision Assessment surveys across PHCs in Bangladesh (24%), Haiti (29%), Malawi (18%), Nepal (4%), and Tanzania (12%) [ 20 ], signifying that low staff and service delivery readiness is common throughout LMICs.…”
Section: Discussionmentioning
confidence: 86%
“…This tool is therefore useful and could be applied across the Zambia health sector at first- and second-level hospitals. In addition, this tool could be applicable to other LMICs to map their efforts to address NCD goals and defining priorities [ 13 , 14 ]. One challenge with the tool however, was the variation brought about by the presence or absence of specific variables which were weighted similarly without regard to their relative importance.…”
Section: Discussionmentioning
confidence: 99%
“…Lack of adequate staff training is a recurring challenge in health program implementation in LMICs. [16][17][18] These results inform initial training and longitudinal re-training activities before and during the Hypertension Treatment implementation in Nigeria Program, given the fundamental need for training and supportive supervision. Further investments in staff and staff training and development and implementation of standing orders for managing CVD and hypertension may be needed to keep pace with these conditions' growing burden.…”
Section: Staff and Service Deliverymentioning
confidence: 63%
“…15 This contrasts with the 2018 report from Garcia de Quevedo et al, who identi ed limited NCDs workforce as a challenge in Mozambique, Colombia, and the Dominican Republic based on the high rate of temporary contract workers for NCD-related care. 16 Moucheraud reported low staff and training readiness scores for NCD diagnosis and management using Service Provision Assessment surveys across PHCs in Bangladesh (24%), Haiti (29%), Malawi (18%), Nepal (4%), and Tanzania (12%), 17 signifying that low staff and service delivery readiness is common throughout LMICs. These differences between the current study and data reported by Garcia de Quevedo et al and Moucheraud are due, at least in part, to the current study's inclusion criterion of PHCs with at least two full-time health workers for Hypertension Treatment in Nigeria Program implementation.…”
Section: Staff and Service Deliverymentioning
confidence: 99%